Coronary Endothelial Dysfunction Is Associated With Elevated Serum PCSK9 Levels in People With HIV Independent of Low‐Density Lipoprotein Cholesterol. Issue 19 (2nd October 2018) - Leucker, Thorsten M.; Weiss, Robert G.; Schär, Michael; Bonanno, Gabriele; Mathews, Lena; Jones, Steven R.; Brown, Todd T.; Moore, Richard; Afework, Yohannes; Gerstenblith, Gary; Hays, Allison G.
Abstract : Background: HIV+ people are at increased risk of coronary artery disease, but the responsible mechanisms are incompletely understood. Proprotein convertase subtilisin/kexin type 9 (PCSK9) is traditionally recognized for its importance in cholesterol metabolism; however, recent data suggest an additional, low‐density lipoprotein receptor–independent adverse effect on endothelial cell inflammation and function. We tested the hypotheses that PCSK9 levels are increased and that abnormal coronary endothelial function is related to PCSK9 serum levels in HIV+ individuals. Methods and Results: Forty‐eight HIV+ participants receiving antiretroviral therapy with suppressed viral replication, without coronary artery disease, and 15 age‐ and low‐density lipoprotein cholesterol–matched healthy HIV− subjects underwent magnetic resonance imaging to measure coronary endothelial function, quantified as percentage change in coronary artery cross‐sectional area during isometric handgrip exercise, an endothelial‐dependent stressor; and blood was obtained for serum PCSK9 and systemic vascular biomarkers. Data are presented as mean±SD. Mean serum PCSK9 was 65% higher in the HIV+ subjects (302±146 ng/mL) than in the HIV− controls (183±52 ng/mL, P <0.0001). Coronary endothelial function was significantly reduced in the HIV+ versus HIV− subjects (percentage change in coronary artery cross‐sectional area, 2.9±9.6% versus 11.1±3.7%; P <0.0001) and inversely related to PCSK9 ( R =−0.51, P <0.0001). Markers of endothelial activation and injury, P‐selectin and thrombomodulin, were also significantly increased in the HIV+ subjects; and P‐selectin was directly correlated with serum PCSK9 ( R =0.31, P =0.0144). Conclusions: Serum PCSK9 levels are increased in treated HIV+ individuals and are associated with abnormal coronary endothelial function, an established measure of vascular health.